MAKNA LIPA SABBE DALAM FILM ATHIRAH (ANALISIS SEMIOTIKA ROLAND BARTHES) - Sari, Yuni Permata; Yesicha, Chelsy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Silk sarong fabric (lipa sabbe) is a typical Bugis Makassar woven fabric woven by Bugis Makassar women. Silk sarong woven fabric (lipa sabbe) is a Bugis tribal cultural heritage that has various motifs, both traditional, semi traditional, and modern. As in the Athirah film which describes the silk sarong woven fabric that has value and meaning as part of the wearer's self and the identity of the Bugis woman, a very sacred object that becomes a heritage for Bugis women. The purpose of this research is to find out the meaning of denotation, connotation and myth as well as the message to be conveyed in the Athirah film by Riri Riza This study uses descriptive qualitative reasearch methods. Data collection techniques used in this study are documentation, observation and literature study. The subject was determined based on purposive technique consisting of the selection of scenes that depicted woven silk sarong (lipa sabbe). Data analysis techniques were performed using Roland Barthes semiotics analysis with data validity checking techniques, namely source triangulation.The result of this research is first, the denotation meaning contained in this film is lipa sabbe is proff of Bugis women’s loyalty. The connotation meaning contained in this film is lipa sabbe is a symbol of the strength of love and pride towards the husband. As well as the meaning of the myth depicted in this film is lipa sabbe is the cultural heritage of the Bugis tribe marriage from the husband’s mother to women as a blessing and an mandate to remain patient an loyal to the husband. Second, the message of the film are lipa sabbe is an inheritance of inherent in the soul of female bugis so that as a female bugis must be stronger figure, keep fighting and be loyal to her husband.Keyword : Films, Semiotics, Lipa Sabbe